Determinants of Early Versus Delayed Neurological Deterioration in Intracerebral Hemorrhage: The INTERACT-2 Study. Issue 6 (June 2019) - You, Shoujiang; Zheng, Danni; Delcourt, Candice; Sato, Shoichiro; Cao, Yongjun; Zhang, Shihong; Yang, Jie; Wang, Xia; Lindley, Richard I.; Robinson, Thompson; Anderson, Craig S.; Chalmers, John
Abstract : Background and Purpose—: We investigated factors associated with early and delayed neurological deterioration (END and DND, respectively) after acute spontaneous intracerebral hemorrhage in the main INTERACT (Intensive Blood Pressure Reduction in Acute Cerebral Hemorrhage Trial)-2. Methods—: INTERACT-2 was a randomized trial of early intensive versus guideline-recommended blood pressure lowering in hypertensive intracerebral hemorrhage (<6 hours from symptom onset) patients. END and DND were defined as a ≥4-point increase on the National Institutes of Health Stroke Scale or ≥2-point decrease on Glasgow Coma Scale, in periods baseline to 24 hours and 24 hours to 7 days, respectively. Multivariable logistic regression models were used to determine independent predictors of END and DND and 90-day outcomes (death and dependency on the modified Rankin Scale). Results—: Of 2598 participants, 450 (17.3%) had either END or DND. Non-China recruitment, higher systolic blood pressure, larger baseline hematoma volume, left hemisphere hematoma location, intraventricular hemorrhage, subarachnoid extension, heterogeneous hematoma density, and cerebral white matter lesions, were predictors of END (all P ⩽0.045). Higher systolic blood pressure, lower diastolic blood pressure, higher glucose, larger baseline hematoma volume, intraventricular hemorrhage, lobar location, brain atrophy, and heterogeneous hematoma density were predictors of DND (all P ⩽0.042). END and DND were both related to death, and death or major disability (modified Rankin Scale scores of 3–6), in adjusted analyses ( P <0.001). Conclusions—: Common variables, most directly related to the intracerebral hemorrhage morphology and underlying cerebral features, determine END and DND and their influence on poor outcomes of death and major disability. Clinical Trial Registration—: URL: https://www.clinicaltrials.gov . Unique identifier: NCT00716079. Abstract : Supplemental Digital Content is available in the text.